Concentrations and Yields of Total Hg and MeHg in Large Boreal Rivers Linked to Water and Wetland Coverage in the Watersheds. Issue 5 (20th May 2022) - Fink‐Mercier, Caroline; Lapierre, Jean‐François; Amyot, Marc; del Giorgio, Paul A.
Abstract: Large rivers are major contributors of mercury (Hg) fluxes to the ocean, as they integrate processes of loading and loss occurring at the watershed level. Stream‐scale studies have revealed that specific landscape properties, such as wetlands or lakes, are hotspots for Hg and methylmercury (MeHg) loading, sinks and transformation, but we still do not know how they operate at the whole network scale and over large geographic gradients. In this study, we evaluate how landscape metrics are related to riverine concentrations and yields of total Hg and MeHg in 18 large boreal rivers draining watersheds ranging from 44 to 209, 453 km 2, distributed along a 650 km latitudinal transect in the James Bay region of Québec. Our analyses of landscape metrics using elastic net models and mixed models reinforce the role of wetlands as sources of MeHg, but further show that surface coverage of water in the watershed is the major driver of both Hg and MeHg concentrations and fluxes at the whole network scale. Our findings also demonstrate that seasonality modulates the relationship between landscape properties and Hg forms. Based on hydrologic data, we additionally estimate annual fluxes for the whole Eastern James Bay to 441 kg Hg and 14.6 kg MeHg, and average landscape yield to 1.24 g Hg km −2  y −1 and 0.041 g MeHg km −2  y −1 . Our study provides tools to broadly predict riverine Hg concentrations and fluxes with only a few easily accessible landscape metrics, which were shown to be better predictors than physico‐chemical variables. Plain Language Summary: Large rivers flux an important amount of Hg, a toxic metal, from land to the ocean. Quantifying these fluxes remains a challenge, particularly in northern environments, because of limited data availability and incomplete understanding of the factors responsible for these fluxes over large landscapes with contrasting climate and land cover (e.g., abundance of vegetation, wetlands, and water). In this study, we show that high abundance of wetlands in northern landscapes is linked to elevated MeHg, a very toxic form of Hg, in 18 northern Canadian rivers distributed across a 650 km latitude gradient. Increasing coverage of lakes and reservoirs, however, leads to lower concentrations and yields of both Hg and MeHg at the mouth, suggesting that aquatic ecosystems as a whole act as a sink, removing large amounts of mercury as water flows downstream. Based on river discharge measurements, we estimated that 441 kg Hg and 15 kg MeHg are transported to James Bay annually. Our study is important as it quantifies mercury fluxes from a region with little data available, and provides tools to broadly predict these fluxes in northern rivers from geographic data that are easily accessible to scientists and that are better predictors than physico‐chemical variables. Key Points: The relative coverage of surface water in the watershed is the most important driver of Hg and MeHg concentrations in these boreal river Seasons modulate the effect of surface water and wetland coverages on Hg and MeHg concentrations through the effect of hydrology on inputs and retention We estimate annual flux to Eastern James Bay at 441 kg Hg and 15 kg MeHg and average yields to 1.24 g Hg km −2 y −1 and 0.041 g MeHg km −2 y −1